Dissociated findings of repetitive nerve stimulation test among intrinsic hand muscles in myasthenia gravis. Issue 6 (8th August 2016) - Matsumoto, Hideyuki; Akahori, Tsugumi; Yasaka, Kyoko; Unuma, Atsushi; Hashida, Hideji
Abstract: The patient was an 82‐year‐old woman who presented with severe respiratory failure and required a ventilator. Neurological examinations showed consciousness disturbance, ptosis, poor eye and respiratory movements, and generalized muscular weakness. A repetitive nerve stimulation test clearly showed waning in abductor pollicis brevis, but not in abductor digiti minimi. The treatments were effective. Later, a blood examination was positive for anti‐acetylcholine receptor antibodies. Therefore, we made a diagnosis of myasthenia gravis (myasthenic crisis). After her recovery, a repetitive nerve stimulation test showed waning in abductor pollicis brevis, but not in abductor digiti minimi or first dorsal interosseous. We must note that the repetitive nerve stimulation test findings can differ among intrinsic hand muscles in myasthenia gravis. We also caution that the repetitive nerve stimulation test findings of some muscles can be normal even in myasthenic crisis.